Accents of Chopin anniversaries in territories annexed by Prussia - Piotrowska, Magdalena (Interdisciplinary Studies in Musicology, 2018)
This article discusses the way in which the Chopin Year of 1910 was celebrated in Wielkopolska. It presents a script prepared in the nineteenth century and shows similarities with celebrations of Mickiewicz and other Polish heroes and artists. Invariably used in such commemorations was a “symbolic capital” that made it easier to create an intergenerational code, thereby disseminating knowledge of national culture and history. A significant role was played in 1910 by a centenary panel, which produced “Guidelines for popular Chopin celebrations” and also many occasional, popular materials. Chopin’s induction into the national pantheon involved the use of audio material (vocal and instrumental concerts), verbal material (articles, poems, lectures and brochures) and also a visual code (anniversary window stickers, tableaux vivants or tableaux illuminés). Illuminated pictures - recommended by a catalogue of slides produced in Poznań - stimulated the imagination of the masses and served as a guide through the composer’s life and work, and their impact was enhanced by a commentary. Most of the living pictures were probably inspired by Henryk Siemiradzki’s canvas Chopin grający na fortepianie w salonie księcia Radziwiłła [Chopin playing the piano in Prince Radziwill’s salon] and Józef Męcina Krzesz’s painting Ostatnie akordy Chopina [Chopin’s last chords]. This combination of codes made it possible to create a model adapted to the times and to the expectations of a mass audience. The Chopin anniversary, in which admiration was inseparably intertwined with manipulation, was a pretext for strengthening the national identity.